Analisis Hutang Dan Modal Kerja Dalam Meningkatkan Kinerja Keuangan Pada PT Perkebunan Nusantara IV Medan - Faras Abiyyu Zhafran; Yenni Samri Juliati Nasution; Nur Fadhilah Ahmad Hasibuan (UNIVED Press, 2023)
This study aims to analyse how debt and working capital in improving financial performance as measured by using profitability, liquidity and solvency ratios at PT Perkebunan Nusantara IV Medan Based on the results of the study, it can be concluded that debt at PT Perkebunan Nusantara IV Medan in 2018-2022 experienced fluctuations. The highest increase in debt was 16.6% while the decrease in debt was 0.6%. The increase in debt is due to an increase in short-term and long-term debt each year. In this study, debt has not been able to increase the profitability (ROA) of the company. Working capital at PT Perkebunan Nusantara IV Medan in 2028-2022 experienced fluctuations. The largest decrease in mode is 2870.6% while the largest increase is 351.3%. The decrease in working capital is due to the increase in current debt higher than current assets. Working capital has not been able to be utilised optimally in increasing the profitability (ROA) of the company. The company's average leverage also shows above 90%, indicating that the company's financial performance is not good. Companies that require large investments in fixed assets such as property, plant and equipment often have higher DER ratios because they tend to use debt to finance these assets.